2014
DOI: 10.1002/14651858.cd007238.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late initiation of epidural analgesia for labour

Abstract: There is predominantly high-quality evidence that early or late initiation of epidural analgesia for labour have similar effects on all measured outcomes. However, various forms of alternative pain relief were given to women who were allocated to delayed epidurals to cover that period of delay, so that is it hard to assess the outcomes clearly. We conclude that for first time mothers in labour who request epidurals for pain relief, it would appear that the time to initiate epidural analgesia is dependent upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 22 publications
2
61
1
4
Order By: Relevance
“…Mode of labor epidural analgesia, as well as the moment in labor stage when it has begun (assessed as cervix dilatation) does not seem to influence type of delivery in our sample, data consistent with the most recent discussions on the subject [27].…”
Section: Predictive Factorssupporting
confidence: 91%
See 1 more Smart Citation
“…Mode of labor epidural analgesia, as well as the moment in labor stage when it has begun (assessed as cervix dilatation) does not seem to influence type of delivery in our sample, data consistent with the most recent discussions on the subject [27].…”
Section: Predictive Factorssupporting
confidence: 91%
“…Data from observational studies have suggested an association between cesarean delivery and the initiation of neuraxial analgesia during early labor (usually defined as cervical dilation less than 4-5 cm) [23,24]. However, meta-analysis of the literature determined that the timing of neuraxial analgesia does not affect the frequency of cesarean delivery [25,27].…”
Section: Neuraxial Analgesia and Mode Of Deliverymentioning
confidence: 99%
“…Reports from other countries have shown that obstetrical outcomes do not differ markedly between the early and late initiation of epidural analgesia after labor has started . However, those data were based on non‐Japanese populations, and whether or not the perinatal outcomes between early and late initiation of epidural analgesia during labor would share the same relationship in a Japanese population was unclear.…”
Section: Introductionmentioning
confidence: 98%
“…However, administering epidural analgesia as part of routine, compared to administration on request, has been found to increase the probability of a cesarean section 174 . The timing of the epidural, i.e., early or late in the first stage of labor, has not been found to influence the risk of cesarean section 175 .…”
Section: Epidural Analgesiamentioning
confidence: 95%